Design Online Project-Base Learning for Learning to Write Scientific Works in Arts and Culture Education - Efendi, Harianto (PT. Riset Press International, 2023)
The purpose of this study is to design a project-based learning model specifically for academic writing in the field of arts and culture in the Scientific Writing course. This research is in the form of learning design research. The design model adopted is a Backward Course Design, the model is designed by positioning the learning outcomes as the starting point for preparing the design. Data analysis was carried out by reviewing teaching material documents and learning model syntax. The design results obtained based on the phases are (1) the real form of learning outcomes in the form of articles in national scientific journals, (2) an evaluation method for assessing process performance and two forms of assessing project results, and (3) an instructional methodology that combines project-based learning syntax, syntax learning academic writing, and lecture syntax for 16 meetings. The resulting learning design is a best practice recommendation to support the teaching of cultural arts academic writing, especially for online learning.